Realtime monitoring for groundwater level and local climate based on universal communication system - Rony Teguh; Hepryandi Usup (Computer Science and Information Technologies, 2021)
The groundwater level and weather patterns and climate conditions are several of the very significant factors which influence the quality of livelihood and the other activity of the tropical peatland environment. The current method of groundwater level and meteorological information aggregate build the use of certain expensive weather station devices, prominent to a lack of vast monitoring suitable to cost barriers and disturbance in some countries. In this research, we have developed and implemented a hardware module based on an Arduino microcontroller and mobile communication, which measures the groundwater level and meteorological data, including air temperature, air humidity, and soil temperature, and humidity, rainfall in peatland area. The data groundwater level is received by a specially developed application interface running on an internet of things (IoT) connected through a global mobile system (GSM) communication. In this work, our proposed system is a model system that can able to generate alerts based on the real-time groundwater level and data weather as potential peat fire in Indonesia. It provides online and data real-time monitoring. In this works, we have resulted in a system to monitor the groundwater level and data weather alert, condition mapping, and warn the people from its disastrous effects.